Mini Oreo Cup Production Plan with Aggregate Method to Minimize Production Costs - Vera Nova Lumban Raja (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2022)
Manufacturing companya PT.Sinar Jatimulia Gemilang produces many types of plastic packaging, one of which is mini oreo cups.The production system in this company is based on job shop, changing product demand and limited product capacity make it difficult for the company to make a productin plan. The purpose of this research is to make a mini cup production plan to meet future demand with the aim of minimize production costs. At the initial stage a field study was conducted to obtain to required data. The data obtained through interviews with production employees from the company. Then do the literature study through books and articles from related journal as the theoretical basis used in this research. Production planning research using exponential smoothing forecasting method with α=0.6 and standard error of 617814.3 was selected with the criteria of the smallest mean square error and aggregate planning.The result of analysis I strategy of inventory level inventory cost is IDR. 441,654,900. In analysis II the strategy for variation in the number workers costs is IDR. 747,373,500. The cost for analysis III subcontracting strategy is IDR. 79,065,843,000. From the research that production cost before the calculation is IDR. 52,002,000,000 and the number of workers is 4. After the result of the research on optimization the number of workers that will be used by 2.